# x^3+y^3

### Factorization of x3 + y3

It can be seen in most book that x3 + y3 can be factorized by dividing the expression by  (x + y).  After division we get a quotient of  (x2 - xy + y2) with no remainder.  Therefore Bạn đang xem: x^3+y^3

However, this method involves knowing the factor (x + y) beforehand (and the understanding of Factor Theorem). This article đơn hàng with different methods of handling this factorization.

(Method 1) (Binomial theorem)  = Move the last two terms vĩ đại the other side, we get: =  (Method 2) Move the last two terms vĩ đại the other side  = (Method 3) (add a term and subtract the same term) = Xem thêm: iq trung bình của người

= = = (Method 4)

Similar to (Method 3), you may start with subtracting a term and adding the same term: Can you continue with the factorization by grouping method?

(Method 5)      (change variable)

Consider  y = u V x   (1) = = ,      by (1), u = x + y

= = M        Replacing nó by (-y), you can get a new identity :  (Exercise)    Prove by following the methods above. Be careful vĩ đại note the sign of the identity.